Improving Library Service Delivery by the Instrumentality of Knowledge Management Practices: A Critical Review - Igbinovia, Magnus Osahon (Folia Toruniensia, 2022)
Purpose: The paper critically examines the nexus between Knowledge Management Practices (KMP) and service delivery in libraries through a detailed review of relevant literature. Special attention was placed on university libraries given their relatively robust system and structures for KMP. The paper also explores how the Socialization, Externalization, Combination and Internalization (SECI) model of Knowledge Management (KM) serves as a tool for the improvement of service delivery in libraries. Method: The approach employed in this study is the critical review of literature. Result: The effective management of knowledge reflected in its creation, organization, sharing and use significantly influences service delivery in libraries. Also, the paper revealed that the SECI model serves as an effective guide in adopting KMP for the improvement of service delivery in libraries. Conclusion: KMP is an influencing factor in the improvement of service delivery in libraries regardless of their type and size.